Working capital management performance of firms listed on Bursa Malaysia / Abu Thahir Abdul Nasser ... [et al.] - Abdul Nasser, Abu Thahir; Samat, Omar; Ibrahim, Zin; Abdul Wahid, Emelin; Amiruddin Othman, Ahmad Marzuki (Research Management Institute (RMI), 2012)
This research paper investigated the working capital management (WCM) performance of 252 firms listed on Bursa Malaysia and identifed practices and policiesfor WCM to enhance efficiency in cash flow from operations. It also determined whether the size, profitability, inventory, and the current assets financing policy could enhance the WCM performance. The variables were 'Cash Conversion Efficiency' (CCE), afinancial performance measure, and 'Overall Working Capital Performance Ranking', a non-financial performance indicator. The findings revealed that the inventory, size, and profitability had significantly influenced the WCM performance. It was also identified that there was a mild positive relationship between the aggressive methodofworking capital financing and the CCE; and the ideal WCM practices and working capital (WC)financing policies to be adopted in firms to maximise the wealth ofthe shareholders.